Investigation On Supply Chain Productivity: A Study In Private Hospitals Malaysia - Tan, Khai Pheng (2012)
This study aims to investigate the extent to which supply chain productivity practices is implemented among private hospitals in Malaysia. In this study, the influence of the determinants on service supply chain performance, as well as the impact of the service supply chain performance on supply chain productivity have been explored. In addition, the role of service supply chain performance in the relationship between the determinants and supply chain productivity has also been assessed. To explore findings, a questionnaire survey was conducted through mail. The questionnaire surveys have been sent to all private hospitals in Malaysia. Out of 124 questionnaires sent out, 74 questionnaires were received, resulting in a response rate of 59.68%. Based on the results obtained, all three determinants (people, process, and technology) were found having positive impact on service supply chain performance in terms of both cost and quality.